Profit Management In The View Of Islamic Business Ethics - M. Noor Bustomi; Indah Maslaha; Achmad Basofitrah; Imelda Musarofah; M. Jamaluddin Affan (HARAMAIN: Jurnal Manajemen Bisnis, 2025)
This study aims to critically investigate the practice of profit management through the lens of Islamic business ethics within the Indonesian corporate context. While profit management is often viewed as a technical accounting maneuver, this research deconstructs its moral implications by integrating prophetic values—shiddiq (honesty), amanah (responsibility), tabligh (transparency), and fathanah (intelligence)—as a framework for financial integrity. A qualitative descriptive approach was employed, utilizing a systematic library research method. The study synthesized 10 primary and secondary sources, including Quranic texts, Hadith, and contemporary academic journals indexed in major databases. Content analysis was applied to reconcile the tension between conventional agency theory and the Maqasid al-Shari’ah framework, focusing on how spiritual internalisation moderates opportunistic managerial behaviour. The results reveal a significant paradigm shift; profit management is categorized into two domains: 'permissible' when aimed at organizational stability (maslahah) without deceit, and 'prohibited' (haram) when it involves tadlis (manipulation) or khiyanah (breach of trust). The study finds that in Indonesia, the "sharia label" does not automatically guarantee superior earnings quality unless supported by robust spiritual governance. Furthermore, an "ethics gap" persists where technical accounting flexibility is frequently exploited to meet market expectations, often sidelining transcendental accountability. This study is limited to a literature-based synthesis and calls for future empirical phenomenological research to explore the psychological-spiritual dimensions of managers. It implies that regulators, such as the OJK and Sharia National Board (DSN-MUI), should enhance the technical accounting competency of Sharia Supervisory Boards to mitigate asymmetric information effectively. This research contributes to Islamic accounting theory by proposing a holistic model that bridges the gap between legalistic compliance and substantive ethical integrity, offering a new perspective on corporate governance in emerging Islamic markets.